Efficacy of different types of transcranial magnetic stimulation on post-stroke aphasia patients: a network meta-analysis - Li, Pei; Xiao, Renyan; Gong, Meng; Jia, Peng; Jin, Song (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the comparative efficacy of repetitive transcranial magnetic stimulation (rTMS) for post-stroke aphasia through a network meta-analysis (NMA).MethodsWe systematically searched four international databases (PubMed, Cochrane Library, Web of Science, and Embase) and three Chinese databases (CNKI, Wanfang Data, and VIP) from inception through October 2024. Two reviewers independently performed literature screening, data extraction, and quality assessment. Discrepancies are resolved through third-party adjudication. Network meta-analysis was conducted using Stata 17.0.ResultsThirty-eight randomized controlled trials (RCTs, n = 1,982) were included, and the NMA results showed that (1) Low-frequency rTMS (LF-rTMS) in combination with High-frequency rTMS (HF-rTMS) (LF-rTMS & HF-rTMS) showed well performance in all indicators (2); intermittent theta-burst stimulation (iTBS) exhibited well benefits for comprehension and repetition domains (3); Continuous theta-burst stimulation (cTBS) showed superior efficacy in naming (4). Stimulation of the pars opercularis (POp) was superior to the pars triangularis (PTr) within the inferior frontal gyrus (IFG) (5). Anatomical landmarks (AL) was the predominant targeting method.ConclusionLF-TMS & HF-TMS is the most effective intervention for clinical treatment of post-stroke aphasia. When targeting the IFG, POp is the optimal stimulation site. Regarding targeting methods, the 10–20 EEG system currently has the strongest evidence base.